Feeding behavior of patients with type 2 diabetes living at Cotonou, Benin. - ALASSANI, ADEBAYO; DOVONOU, ALBERT; Gninkoun, Jules; WANVOEGBE, FINANGNON ARMAND (My University, 2016)
Objectives: The objective of the study is to assess the feeding behavior of diabetic patients. Methodology: This is a cross-sectional and descriptive study that was conducted among type 2 diabetes followed at the screening, monitoring and treatment center in Cotonou. Eating behavior was assessed through the food diary for 72 h. Results: In total 107 patients were included in the study. Sex ratio was 0.52. The mean age of the target population was 53.95 ± 11.36 years. Energy intake is high in 19 patients (17.75%). Fruit and vegetable consumption was normal in only 6 patients (5.61%) and 68 patients (63.55%) acceptable food consumption score. Conclusion: Analysis of the feeding behavior of type 2 diabetes noted deficiencies. Improve nutrition through patient education is needed.
Keywords: feeding diabetics Cotonou Benin